2016
DOI: 10.22495/rgcv6i1art8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of holt-winters triples exponential smoothing and seasonal Arima: Forecasting short term seasonal car sales in South Africa

Abstract: In this paper, both Seasonal ARIMA and Holt-Winters models are developed to predict the monthly car sales in South Africa using data for the period of January 1994 to December 2013. The purpose of this study is to choose an optimal model suited for the sector. The three error metrics; mean absolute error, mean absolute percentage error and root mean square error were used in making such a choice. Upon realizing that the three forecast errors could not provide concrete basis to make conclusion, the power test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Yaffee and McGee (2000) have suggested that model parameter estimates must be less than one as to deem them to be sufficient and significant. The same results are also obtained by Makatjane and Moroke (2016) in their study of comparative of Holt-Winters triple exponential smoothing and Seasonal ARIMA models.…”
Section: Results and Analysis Of Sarima Modelsupporting
confidence: 77%
See 3 more Smart Citations
“…Yaffee and McGee (2000) have suggested that model parameter estimates must be less than one as to deem them to be sufficient and significant. The same results are also obtained by Makatjane and Moroke (2016) in their study of comparative of Holt-Winters triple exponential smoothing and Seasonal ARIMA models.…”
Section: Results and Analysis Of Sarima Modelsupporting
confidence: 77%
“…Comparative analysis: The purpose of this section is to determine the model which best mimics the data and produces fewer forecasts. With the extension to Makatjane and Moroke (2016) methodology, the current study follows up with the application of four error metrics which are a mean error, mean absolute error, mean percentage error and mean absolute percentage error to measure the performance of each model and results are summarized in Table 3. The results indicate that the model with intervention has the smallest values of all the proposed error metrics.…”
Section: Sarima-intervention Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Carriero et al (2015) forecasting performance is checked to discover the best performing model and utilised the three error measurements; to be specific; mean square error (MSE), mean absolute error (MAE) and mean absolute percentage error (MAPE). In any case, the present study tails these methods of Carriero et al (2015) and Makatjane and Moroke (2016) …”
Section: Forecasting Performance Ofmentioning
confidence: 99%